Redefinition of Cosmolaelaps Berlese (Acari: Laelapidae) and description of five new species from Brazil - Moreira, Grazielle Furtado; Klompen, Hans; Moraes, Gilberto José De (Zootaxa, 2014)
Cosmolaelaps Berlese, 1903 was originally described as a subgenus of Laelaps Koch. More recently, this group has been treated at the generic level or as a subgenus of Hypoaspis Canestrini, 1885. One of the objectives of the present paper is to provide a detailed characterisation of Cosmolaelaps, here considered at the generic level, a group that was poorly characterised in its original description as well as in subsequent publications. It is most closely related to Stratiolaelaps Berlese, from which it can usually be distinguished by the presence of extra paired and unpaired setae on the opisthonotal region of the dorsal shield, as well as by not having hypertrophied chelicerae or corniculi. A total of 108 species belong to Cosmolaelaps, including the new species described here. Five other species may also belong to this genus, but the available published information does not allow their conclusive placement. The Brazilian fauna of Hypoaspidinae is poorly known, but Cosmolaelaps seems to be well represented in Brazil. Thus, the second objective of this paper is to describe five new species of Cosmolaelaps from that country, namely C. barbatus sp. nov., C. busolii sp. nov., C. confinisetarum sp. nov., C. jaboticabalensis sp. nov. and C. oliveirai sp. nov.